Anthology of children's literature - Johnson, Edna. (Boston : Houghton Mifflin, 1977)
An anthology of nursery tales and rhymes, nonsense verse, poetry, folklore, mythology, epics, fiction, and non-fiction from a variety of sources.
First ed. compiled by E. Johnson and C. Scott; 2d ed. by E. Johnson, C. E. Scott, and E. R. Sickels; 3d-4th eds. by E. Johnson, E. R. Sickels, and F. C. Sayers.
Includes bibliographies and index.
Keywords: Children's literature; Literature -- Collections